Hubungan Keabsahan Pengalihan Piutang (Cessie) Yang Dilakukan Secara Berulang Kali Terhadap Perpindahan Hak Tanggungan Milik Debitur - Novelia Adistie; Jarkasi Anwar (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Banking helps people, one of which is through credit facilities. Received credit is accompanied by submitting a guarantee imposed by the mortgage right to the bank or creditor. One of the problems that often occur in credit is bad credit. The solution to overcome this is by obtaining funds relatively quickly by banks through transfer of accounts receivable (cessie). Efforts to minimize an impact that can harm the parties in the process of transferring accounts receivable (cessie) are at the core of the problems raised in this study, namely, how is the relationship between the legality of the transfer of accounts receivable (cessie) which is carried out repeatedly to the transfer of the debtor's liability and how is legal protection? for cessie buyers (cessionaris) based on Article 613 of the Civil Code in conjunction with Law Number 4 of 1996 concerning Land Mortgage Rights and Land-related Objects. The research was conducted using a normative juridical research method with descriptive analytical research using a statutory approach method. The data sources used in this research are primary legal materials, secondary materials, and tertiary legal materials. The data collection technique used in this research was through literature study and then analyzed qualitatively and normatively. The results of the research conclude that, the relationship between the legality of the transfer of accounts receivable (cessie) which is carried out repeatedly on the transfer of the debtor's mortgage is known to have mutual influence. A legal cessie is carried out if the basis of the rights is valid and in accordance with Article 613 and Article 1320 of the Civil Code. Legal protection for cessie buyers (cessie) in the practice of transferring accounts receivable (cessie) which is carried out repeatedly for the transfer of the debtor's mortgage is carried out through a cessie deed and several regulations in Law Number 4 of 1996 concerning Mortgage Rights to Land with Objects Items related to land.